2017
DOI: 10.1007/s12594-017-0668-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bearing Capacity of Near-Surface Soils Using Integrated Methods: A Case Study of Otukpa, Ogbadibo Lga, Benue State, North-Central Nigeria

Abstract: The load bearing capacity of soils in Otukpa area of Benue state, Nigeria was evaluated by characterizing the geotechnical, geophysical and structural properties of the soil. The evaluation was necessary because aside the area holding good prospect for future increase in human population, sparsely distributed low-weight buildings in the area have cracks and other signs of failure. Remote sensing/GIS, geophysical and geotechnical approaches were integrated to achieve the objective. 2-D tomography and processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The consistency indices, which measures the degree of coherence between soil particles at a given water content, show values that are very close to negative; hence explaining why the soils couldn't behave as liquid, but only as soft to hard material. The observations also suggest that since the soilsgenerally have relatively similar consistency, they would all behave in a similar manner when extra water is added to them [1]. However, it is pertinent to note that excess water content (and some other external factors) can interfere their consistency.…”
Section: Compaction Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The consistency indices, which measures the degree of coherence between soil particles at a given water content, show values that are very close to negative; hence explaining why the soils couldn't behave as liquid, but only as soft to hard material. The observations also suggest that since the soilsgenerally have relatively similar consistency, they would all behave in a similar manner when extra water is added to them [1]. However, it is pertinent to note that excess water content (and some other external factors) can interfere their consistency.…”
Section: Compaction Resultsmentioning
confidence: 75%
“…5). Soils with similar specific gravity show similarity in textural and mineralogical makeup [1]. These soils are mainly medium-coarse grained materials (except for OKJ).…”
Section: Compaction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect a little pore pressure to build up as a result of the low permeability that will result. This pore pressure will not affect structures in the area because [14] showed that the water table in the area is at a depth of 201m. …”
Section: Grain Size Distributionmentioning
confidence: 99%
“…The oedometer method of determining the 1D-consolidation of soil was done with one-directional drainage allowed [14]. The calculated consolidation values of C v and M v at a stress level of 250kN are presented as Table 6.…”
Section: Consolidationmentioning
confidence: 99%